Prospective ex-vivo study on thermal effects in human skin phototypes II, IV and VI: a comparison between the 808, 1064, 1210 and 1320-nm diode laser - Leclère, Franck Marie Patrick; Unglaub, Frank (Journal of cosmetic and laser therapy, 2012)
(2012). Prospective ex-vivo study on thermal effects in human skin phototypes II, IV and VI: A comparison between the 808, 1064, 1210 and 1320-nm diode laser. Journal of Cosmetic and Laser Therapy: Vol. 14, No. 1, pp. 7-13.